2018
DOI: 10.1053/j.gastro.2018.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Portosystemic Shunts and Increased Complications and Mortality in Patients With Cirrhosis

Abstract: In a retrospective analysis of almost 2000 patients, we found 60% to have SPSS; prevalence increases with deterioration of liver function. SPSS increase risk for HE and with a chronic course. In patients with preserved liver function, SPSS increase risk for complications and death. ClinicalTrials.gov ID NCT02692430.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
222
8
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 181 publications
(242 citation statements)
references
References 35 publications
10
222
8
2
Order By: Relevance
“…As it would be expected, hepatic encephalopathy was more frequent in this population, confirming what has been described in prior reports . Similarly, ascites seemed to be more frequent in patient groups with SPSSs as described previously by Simón‐Talero et al In their cohort of patients, they found a more extensive plethora of portal hypertension–related signs and complications, including splenomegaly, gastroesophageal varices, gastrointestinal bleeding, ascites, acute kidney injury with hepatorenal physiology, and SBP. The widespread association was more limited in the present study, likely due to our limited and focused population.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…As it would be expected, hepatic encephalopathy was more frequent in this population, confirming what has been described in prior reports . Similarly, ascites seemed to be more frequent in patient groups with SPSSs as described previously by Simón‐Talero et al In their cohort of patients, they found a more extensive plethora of portal hypertension–related signs and complications, including splenomegaly, gastroesophageal varices, gastrointestinal bleeding, ascites, acute kidney injury with hepatorenal physiology, and SBP. The widespread association was more limited in the present study, likely due to our limited and focused population.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, this is the biggest study that clinically correlates the presence of SPSSs prior to LT to outcomes in the post‐LT setting. Our results suggest that after LT surgery, the previously described clinical impact of SPSSs in the population with cirrhosis subsides …”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Moreover, SPSSs could be classified in large or small size according to its maximum diameter, with a cut-off of 8 mm; this value was chosen since it was the smallest size of a symptomatic shunt embolized reported in the literature. 9,10 SPSSs have been described in both patients with cirrhosis and in patients without significant alterations of liver function. 11 The presence of the shunt alters hepatic hemodynamics and increases the bioavailability of intestinally derived agents, such as ammonium, increasing the risk of HE.…”
mentioning
confidence: 99%